2017
DOI: 10.1002/jemt.22946
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of four final irrigation protocols on root canal dentin components by polarized light microscopy and scanning electron microscopy

Abstract: The present study aimed to evaluate the effects of four endodontic chelating agents, followed by 2.5% sodium hypochlorite (NaOCl), as final irrigation regimens on organic and inorganic components of human root dentin. Sixty mandibular incisors were prepared and randomly divided into six groups (n = 10): QMiX, 1% peracetic acid (PA), 17% EDTA, 10% citric acid (CA), 2.5% NaOCl (solution control) and distilled water (DW-negative control). After irrigation with the chelating agents, a final flush was performed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…Eleven studies compared QMix to various irrigants like EDTA [ 23 24 25 26 27 28 29 30 31 33 35 ], 4 studies on MTAD [ 23 31 34 35 ], 5 studies on NaOCl [ 23 27 28 29 33 ], 2 studies on 7% EDTA (SmearClear) [ 30 32 ], 10% citric acid [ 29 33 ], one study on chitosan [ 32 ], glyde [ 32 ], 1% peracetic acid [ 33 ], Tubulicid Plus [ 34 ] and 7% maleic acid [ 28 ]. The effectiveness of smear layer removal was measured by different scoring systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies compared QMix to various irrigants like EDTA [ 23 24 25 26 27 28 29 30 31 33 35 ], 4 studies on MTAD [ 23 31 34 35 ], 5 studies on NaOCl [ 23 27 28 29 33 ], 2 studies on 7% EDTA (SmearClear) [ 30 32 ], 10% citric acid [ 29 33 ], one study on chitosan [ 32 ], glyde [ 32 ], 1% peracetic acid [ 33 ], Tubulicid Plus [ 34 ] and 7% maleic acid [ 28 ]. The effectiveness of smear layer removal was measured by different scoring systems.…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of smear layer removal was measured by different scoring systems. Four studies used Hülsmann et al scoring system [ 25 26 30 35 ], 2 studies used Takeda et al system [ 27 29 ], 3 studies used Torabinejad et al scoring system [ 28 31 34 ] and others included Gishi et al scoring system [ 33 ], Dai et al scoring system [ 23 ] and Rome et al scoring system [ 32 ] respectively. One study did not mention the scoring system and adhered to counting the number of open and closed tubules using imaging software, Adobe Photoshop CS3 [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When used alone inside the root canal, NaOCl is as ineffective as distilled water to remove the smear layer produced during root canal preparation (Torabinejad et al, ; Baldasso, Cardoso, da Silva, Morgental, & Kopper, ). Therefore, some studies have shown that the use of a combination of NaOCl and EDTA is particularly effective in the removal of smear layer and debris (Goldman, Goldman, Cavaleri, Bogis, & Lin, ; Yamada, Armas, Goldman, & Lin ; Baldasso et al, ). EDTA is widely used as a chelating agent and is able to react with calcium ions in hydroxyapatite crystals, removing calcium ion from the dentin (Calt & Serper, ).…”
Section: Discussionmentioning
confidence: 99%
“…EDTA is widely used as a chelating agent and is able to react with calcium ions in hydroxyapatite crystals, removing calcium ion from the dentin (Calt & Serper, ). However, when NaOCl is associated with EDTA, alteration of the organic and inorganic dentin components and erosion are observed (Lottanti, Gautschi, Sener, & Zehnder, ; Baldasso et al, ).…”
Section: Discussionmentioning
confidence: 99%